Proximal spinal muscular atrophy 5q in the Republic of North Ossetia – Alania: population-genetic features, diagnostic problems and treatment prospects - I. S. Tebieva; A. F. Murtazina; S. B. Artemieva; Yu. V. Gabisova; R. A. Zinchenko (Нервно-мышечные болезни)
This study presents the structure and population data of spinal muscular atrophy 5q in the Republic of North Ossetia – Alania. The number of newborns for the period 2000–2020 was 195 954, and the prevalence of spinal muscular atrophy 5q among newborns was 1:24 494, or 4.08 per 100.000. That corresponds to data on other populations of the Russian Federation and the world. We also describe intermediate results of the clinical efficacy of treatment of three spinal muscular atrophy 5q patients. Gene replacement therapy was used in two cases and combined pathogenetic and gene replacement therapy was used in the third case. No clinically significant decrease in the CHOP INTEND score from the baseline level was found in any patient during follow‑up. Clinical improvement was noted both during treatment with nusinersen and after administration of onasemnogene abeparvovec. Described clinical cases demonstrate the importance of early diagnosis and initiation of antisense oligonucleotide and/or gene replacement therapy, which is possible only when spinal muscular atrophy 5q is included in the neonatal screening program.